EFEKTIFITAS COGNITIVE BEHAVIOURAL EDUCATIONAL INTERVENTION PADA PASIEN POST TRANS URETHERAL RESECTION OF THE PROSTATE DI RS PKU MUHAMMADIYAH BANTUL - Wantonoro Wantonoro; M Dahlan (Universitas Aisyiyah Yogyakarta, 2015)
This research aimed to show the effectiveness cognitive behavioural educational intervention (CBEI) in post trans urethral resection of the prostate in PKU Muhammadiyah Bantul Hospital. The research design used Quasi-eksperiment; posttest only control group. Sample was taken by nonprobability sampling with accidental sampling method (on February-June 2015). There were 20 respondent have TURP procedure and which were divided into two groups. The t-test independent indicated a significant difference in pain respon in two groups (p=0,000). From this study, CBEI was recommended for pain management in patient with TURP.Keywords: cognitive behavioural educational intervention, pain, TURP